Emotional understanding in Japanese children 3–6 years: Language ability mediates the relations between theory of mind and executive function - Awoun Jung; Izumi Uehara (PLoS ONE, 2026)
Previous research has documented associations between children’s emotional understanding (EU) and social-cognitive abilities such as theory of mind (ToM) and executive function (EF); however, findings in preschool-aged children remain inconsistent. One potential explanation is that language ability, which develops rapidly during early childhood, has often not been examined concurrently with these abilities. The present study focused on individual differences in EU and examined how ToM, EF, and language ability relate to EU in Japanese preschool children, with particular attention to the mediating role of language. Participants were 90 children aged 3–6 years (M = 60.34 months, SD = 10.82). Children completed a false belief task, emotional understanding tasks, executive function tasks assessing cognitive flexibility and working memory, and a receptive vocabulary test. Correlational analyses, hierarchical multiple regression analyses, and bootstrapped mediation analyses were conducted. EU was positively associated with ToM, EF, and language ability. Language ability accounted for significant variance in EU beyond age and gender. When language ability was included in the model, the association between ToM and EU was no longer significant, whereas the association between EF and EU remained significant but was attenuated. Mediation analyses revealed significant indirect effects of both ToM and EF on EU through language ability, indicating that the association between ToM and EU was accounted for by language ability, whereas EF showed both direct and indirect associations with EU. These findings suggest that language ability plays a central role in linking social-cognitive abilities to emotional understanding in early childhood. Theory of mind was associated with emotional understanding primarily through language, whereas executive function showed both direct and indirect associations via language ability. By modeling multiple predictors simultaneously, this study provides an integrated account of individual differences in emotional understanding and elucidates the distinct pathways through which cognitive and social-cognitive skills are associated with emotional development.